2018
DOI: 10.1007/s00520-018-4178-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of masculinity and body image in men with prostate cancer: the role of exercise

Abstract: Whether treatment includes androgen deprivation or not, men who participate in higher levels of aerobic exercises report higher levels of masculinity, improved body image, and quality of life than those who are inactive. Future longitudinal research is required evaluating exercise level and its effect on masculinity and body image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
2
31
0
3
Order By: Relevance
“…Exercise not only helped participants to improve their mood and energy levels, but also gave them a sense of achievement and control over their body. The present study deepened the latter finding, which was only partially explored by previous literature . Participants defined being able to exercise as a reassuring demonstration of their abilities and strength, despite cancer.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Exercise not only helped participants to improve their mood and energy levels, but also gave them a sense of achievement and control over their body. The present study deepened the latter finding, which was only partially explored by previous literature . Participants defined being able to exercise as a reassuring demonstration of their abilities and strength, despite cancer.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, some studies have supported this preliminary evidence. For example, a correlational study by Langelier et al found that higher levels of aerobic exercise were associated with higher levels of masculinity, improved body image, and QOL in PCa patients …”
Section: Introductionmentioning
confidence: 99%
“…It is clear that prostate cancer and its treatments negatively effect masculinity, body image, and a man's sense of personal identity. While this review supports that exercise provides a number of benefits, levels of exercise are not improving without direct intervention . This highlights the need to address established exercise barriers and preferences .…”
Section: Resultsmentioning
confidence: 80%
“…This theory is supported by a recent cross-sectional study that demonstrated significantly higher scores of masculinity when men achieved recommended levels of aerobic exercise compared with those achieving recommended levels of resistance exercise. 41 However, the small number and heterogeneity between the exercise programs limits our current understanding; thus, future research must address the impact of exercise type on masculinity outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation